PENGARUH MODAL KERJA DAN JENIS BARANG DAGANGAN TERHADAP PENDAPATAN TOKO KELONTONG MADURA DI KECAMATAN JAMBANGAN KOTA SURABAYA - Rifdatul Hanifah; Joko Priyono (Jurnal Nirta : Inovasi Multidisiplin, 2025)
This study analyzes the influence of working capital and types of merchandise on the income of Madurese grocery store owners in Jambangan District, Surabaya. Using a quantitative method with a survey of 60 respondents, the data were analyzed using multiple linear regression, including the t-test, F-test, and coefficient of determination (R²). The t-test results show that working capital has a positive and significant effect on income, while the types of merchandise do not have a significant effect. Meanwhile, the F-test confirms that both variables simultaneously have a significant influence on income. The R² value of 21.7% indicates that the model explains only a small portion of income variation. The study recommends optimizing the use of working capital and adjusting merchandise types according to consumer needs to improve income and business competitiveness.